Laparoscopic repair of Morgagni hernia with extra-abdominal sutures and ileocecal resection for colon cancer: a case report. Issue 12 (20th December 2022) - Hara, Tetsuhiro; Adachi, Tomohiro; Shimbara, Kensuke; Kai, Yuichiro; Honmyo, Naruhiko; Shintakuya, Ryuta; Goda, Noriko; Hanaki, Hideaki; Shimomura, Manabu; Aoki, Yoshiro; Kano, Mikihiro; Tokumoto, Noriaki; et al.
Abstract: Morgagni hernia is a rare form of diaphragmatic hernia. It is located at the anterior edge of the diaphragm and does not have an anterior rim. It is difficult to achieve a secure closure and maintain the tension of closure with laparoscopic surgery. We have performed laparoscopic resection of colorectal cancer and hernia repair simultaneously. An 89-year-old woman underwent laparoscopic hernia repair and ileocecal resection simultaneously. Regarding hernia repair, we considered that it would be difficult to use a mesh from the viewpoint of infection due to the colectomy. Therefore, we have done the extra-abdominal suture method. After laparoscopic ileocecal resection, a small incision was made in the epigastric region, and Morgagni hernia repair was performed with extra-abdominal sutures. She had no recurrence of either colon cancer or hernia for 22 months post-operatively. The extra-abdominal suture method can provide secure closure of the hernia orifice for Morgagni hernia.